Analisis Faktor – faktor yang Mempengaruhi Konsumsi dan Produksi Gula Menuju Swasembada Gula 2019 - Puspitosari, Rosita Riris; Surono, Sulastri (UI Scholars Hub, 2020)
Sugar is a strategic food commodity which is targeted to reach self-sufficiency in 2019 although there are many problems in the Indonesian sugar industry. Sugar self-sufficiency can be realized if domestic sugar production is able to fulfill domestic sugar demand. This study analyzes the factors that influence consumption and production of Indonesian sugar and their implications for the 2019 sugar self-sufficiency target. For white sugar, the estimation using the simultaneous equation system resulted that domestic consumption for white sugar was positively affected by previous year's consumption and domestic production of white sugar was positively affected by sugarcane area and negatively affected by the national sugar price in the previous year. For refined sugar, the estimation using multiple linear regression showed that domestic production for refined sugar is positively affected by the maximum production capacity of refined sugar mills and volume of import raw sugar. Production of refined sugar mills negatively affected by the Rupiah/US exchange rate. The consumption for refined sugar is positively affected by the number of population. The projection shows that the sugar self-sufficiency target in 2019 has not been fulfilled. Nonetheless, the policy of increasing land area, determining the amount of HPP that increases every year and controlling the price of sugar need to be done to increase production and reduce imports.